2003
DOI: 10.1080/03093640308726666
|View full text |Cite
|
Sign up to set email alerts
|

Walking in a vacuumassisted socket shifts the stump fluid balance

Abstract: Gains in stump volume have been documented in trans-tibial amputees while walking in custom made under-sized, total surface-bearing, vacuum-assisted sockets (Board et al., 2001). These gains raised doubts as to whether the sockets were truly under-sized and concerns that using an over-sized socket with vacuum-assist could lead to swelling, resulting, in discomfort or pain. The purposes of the present study were to determine if: (a) walking in a vacuum-assisted socket causes the stump to retain or gain volume i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 6 publications
4
67
1
Order By: Relevance
“…56 Above all, less pistoning may indicate a more natural gait and the amputee is more likely to feel like the prosthesis is a part of their body. 19,63,38 Different methods have been used to evaluate pistoning in lower limb prosthesis, both in static and dynamic positions (Table 3). To date, radiological methods have constituted the more popular methods of measuring the pistoning.…”
Section: Discussionmentioning
confidence: 99%
“…56 Above all, less pistoning may indicate a more natural gait and the amputee is more likely to feel like the prosthesis is a part of their body. 19,63,38 Different methods have been used to evaluate pistoning in lower limb prosthesis, both in static and dynamic positions (Table 3). To date, radiological methods have constituted the more popular methods of measuring the pistoning.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent design was a crossover design (n = 9) [27][28][30][31][32][33][41][42][43], followed by five single-subject/case studies [34][35][38][39]44], four randomized crossover trials [13][14]21,29], and three case series [26,[46][47]. The remaining studies were repeated-measure design (n = 1) [45], randomized controlled trials (n = 2) [22,24], cross-sectional design (n = 2) [36][37], and prospective study (n = 1) [40] Table 1.…”
Section: Methods Of Studiesmentioning
confidence: 99%
“…Five studies reported the effects of VAS and TSB sockets on residual limb volume, from which one study was classified as having robust evidence [13], one as having moderate evidence [21], and three as having weak evidence [35,42,47].…”
Section: Residual Limb Volume Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Both terms differentiate the suspension method from passive suction or valve systems. EVS sockets continue to grow in popularity on the basis of improved fit and function [5][6][7][8] through a reduction of pistoning [5,[9][10][11] and residual-limb volume management [5,[12][13]. A recent systematic review of EVS studies [14] identified only two peer-reviewed journal publication related to the effects of EVS on residual-limb physiology [5,15] and underscores the need for more evidence-based research in this underserved field.…”
Section: Introductionmentioning
confidence: 99%